English Language Learning in Primary Schools: A Bibliometric Review of Trends, Collaboration, and Future Research Directions - Rahyuni Melisa; Litha Nesidekawati Dakka; Eko Saputra Nurdiansa; Wa Ode Siti Wardani (Creative Smart Visionary, 2025)
This study aims to map the research landscape of English language learning in primary schools through a bibliometric analysis. Data were collected from scientific publications spanning 2000 to 2024 and analyzed using VOSviewer. The findings reveal a marked increase in publications, particularly from 2020 onward, peaking in 2022. Language, Culture and Curriculum emerged as one of the most influential journals, while Khon Kaen University was identified as the most prolific contributing institution. Among individual contributors, Halbach A was the most productive author, whereas Al-Issa AS received the highest number of global citations, indicating substantial scholarly influence. Cluster analysis revealed seven major thematic areas, encompassing student and teacher roles, curriculum development, and teacher professionalism. Overlay visualization further highlighted emerging research themes, such as multimodality, gamification, and Content and Language Integrated Learning (CLIL), pointing to future directions in the field. These findings carry significant implications for curriculum design, teacher education, and the development of innovative instructional strategies. Notwithstanding its contributions, this study is limited by the scope of data and analytical methods employed. Future research is recommended to adopt mixed-methods approaches and incorporate multilingual data to achieve a more comprehensive mapping.